(untitled) (Global Journal of Management and Business Research, 2024)
Abstract Our principal objective is to implement a conditional CAPM that in addition to the global market risk specifies the level of market integration evaluates exchange rate risk and accounts for local market risk To investigate the potential for portfolio diversification for foreign investors in this region by examining the impact of financial crises on the evolution of national markets in the MENA region s financial integration with the global market as well as with the three selected developed markets namely France Great Britain and the United State In order to test a conditional version of De Santis and Gerard s ICAPM by admitting a specification of a multivariate GARCH process this line of research has used a particular methodology MGARCH Keywords financial crisis ICAPM international diversification financial integration